(untitled) (Research, Society and Development, 2020)
Objective: reflect the experiences of relatives of women with operated breast cancer, in relation to the psychological impact of the family’s disease on their daily lives, through integrative review. Method: integrative review of the experiences of family members of women with breast cancer already operated, emphasizing the Phenomenology of Perception. Results: family members of women with breast cancer survive stress situations related to the diagnosis of breast cancer in a loved one and the fear of acquiring the disease, due to associated genetic factors, as well as living with a family member are imposed as relevant issues. The woman perceives the size impact of cancer on the lives of family members, which affects the experience of pathology and mutilated body, overseeing guilt and worsening of the psychological suffering in relation to the disease. For Merleau-Ponty, every consciousness is perceptive and the perceived world is the presumed basis of all rationality and existence. Conclusion: the death of women with breast cancer may provide anticipatory mourning in family members, bringing greater anguish to women in coping with surgical pathology. Understanding the experience of women with breast cancer and mutilated in relation to the suffering of family members as loved ones would help nurses to unveil the phenomenon that translates into anxiety in the experience of female breast cancer.